New Kingdom hieratic collections from around the world - Fanciulli, Andrea; Gabler, Kathrin; Izak, Jessica (Presses Universitaires de Liège, 2024)
"This book is the first in a series of volumes designed to provide a detailed overview of the New Kingdom hieratic materials preserved in various museums and public collections around the world. Each volume is arranged geographically and proceeds in alphabetic order—continent by continent and country by country. Volume 1 opens with a complete overview of the New Kingdom hieratic material in the Egyptian Museum in Cairo, which is followed by overviews of 18 European museums and 3 North American collections. The endeavour is directly connected to the interdisciplinary project Crossing Boundaries: Understanding Complex Scribal Practices in Ancient Egypt, a joint venture of the University of Basel, the University of Liège, and the Museo Egizio (Turin). Since 2019, the Crossing Boundaries project has targeted the rich papyrological materials from the village of Deir el-Medina (c. 1350–1050 BCE) held in the Museo Egizio, seeking to enhance our understanding of the scribal practices that lie behind the production of the texts from this community. The driving methodological motto of Crossing Boundaries has been to adopt a contextualized approach to these written documents. As progress was made on the Deir el-Medina materials, the need to develop a clearer picture of all the hieratic texts available from the same period quickly became evident, which is met by the present publication."
Keywords: Inscriptions, Egyptian; Egyptian language / Writing, Hieratic; Egypt / History / New Kingdom, ca. 1550-ca. 1070 B.C; Aufsatzsammlung